1988
DOI: 10.1111/j.1440-1827.1988.tb02321.x
|View full text |Cite
|
Sign up to set email alerts
|

AN AUTOPSY CASE OF DIFFUSE MYELOMATOSIS ASSOCIATED WITH SYSTEMIC KAPPA LIGHT CHAIN DEPOSITION DISEASE (LCDD) A Patho‐anatomical, Immunohistochemical and Immunobiochemical Study

Abstract: A case of systemic light chain deposition disease in a 48‐year‐old man is presented. Clinically, the patient showed the signs of multiple organ (liver, heart and kidney) failure, but multiple myeloma was not diagnosed. Autopsy revealed generalized deposition of hyaline, a Congo red‐negative substance, especially in the arterial walls of various organs. In the bone marrow, myelomatous proliferations of plasma cells positive for kappa light chain were recognized. The deposited substance was ultrastructurally dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…LCDD has been described surrounding parenchymal cells in numerous organs, most commonly liver, heart, and kidney, but also adrenal glands, spleen, pancreas, muscle, choroid plexus, and nerve 4, 16–19. In LCDD, the light chain is more commonly kappa, while in AL amyloidosis, it is more frequently lambda 4, 5, 18, 20. In both their own series of 13 patients and a review of 43 published cases of amyloid myopathy, Spuler et al8 found that the light chain dysproteinemia in amyloid myopathy is most commonly lambda.…”
Section: Discussionmentioning
confidence: 99%
“…LCDD has been described surrounding parenchymal cells in numerous organs, most commonly liver, heart, and kidney, but also adrenal glands, spleen, pancreas, muscle, choroid plexus, and nerve 4, 16–19. In LCDD, the light chain is more commonly kappa, while in AL amyloidosis, it is more frequently lambda 4, 5, 18, 20. In both their own series of 13 patients and a review of 43 published cases of amyloid myopathy, Spuler et al8 found that the light chain dysproteinemia in amyloid myopathy is most commonly lambda.…”
Section: Discussionmentioning
confidence: 99%
“…Although several reports have shown myocardial deposition of immunoglobulin light chains in postmortem examinations, 10,11 the clinical features of LCCM and patient responses to treatment have yet to be elucidated. Left ventricular morphology and transmitral inflow pattern determined by Doppler echocardiography are consistent with diastolic ventricular dysfunction due to restrictive cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…This disease is characterized by the widespread tissue de position of amorphous non-amyloid material con taining monoclonal light chains. These gammaglobu lin fragments are produced in excess by monoclonal plasma cells that are either neoplastic (multiple mye loma) or hyperplastic (benign monoclonal gammopathy) [12][13][14][15][16]. Light-chain nephropathy should be distinguished from the so-called 'myeloma kidney' due to obstruction of tubules by abnormal casts.…”
Section: Discussionmentioning
confidence: 99%